ASSOCIATION OF THE IMPACT OF POSTNATAL NUTRITION ON THE GROWTH OF PRETERM INFANTS <34 WEEKS GESTATIONAL AGE FROM BIRTH TO DISCHARGE - FAUJDAR, JITENDRA SINGH; SINGH, KALPANA; SINGH YADAV, RAJVEER; GUPTA, JITENDRA KUMAR; KAKKAR, MUNISH; ACHARYA, USHA; SINGH, SOURABH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objectives of the study were to measure the actual daily amount of each nutrient (protein, glucose, and fat) energy and fluid as per current ESPGHAN guidelines for preterm infants and to analyze the role of nutrients at different gestational age on growth and weight of preterm infants. Material and Methods: An observational and prospective cohort study was conducted from January 1, 2018, to December 31, 2018. This study included all preterm infants born <34 weeks gestational age admitted in the neonatal intensive care unit during this period at Mahatma Gandhi Medical College and Hospital. A total of 120 preterm neonates were studied. Results: There were mean weight, length, and head circumference continues to rise till the study end. Mean energy at birth was also continues to rise till the end. Conclusion: In the study, proper nutritional supplement as per ESPHAGEN guidelines was used for the development of preterm infant. The study showed that there were statistically significant results with anthropometry parameters with preterm baby growth in all domains.